Access to carbon nanofiber composite hydrated cobalt phosphate nanostructure as an efficient catalyst for the hydrogen evolution reaction - Ahmed, Imtiaz; Biswas, Rathindranath; Sharma, Rohit; Burman, Vishal; Haldar, Krishna Kanta (Frontiers in Chemistry, 2023)
Extremely attractive technology for production of sustainable hydrogen with water electrolyzers was foreseen as one of the most promising way matches with the increasing demands of renewable resources and electricity storage. Mainly the efficient generation of H2, water electrolysis involving hydrogen evolution reactions (HER) depends on efficient and affordable electrocatalysts. Hydrogen is an effective fuel that can be produced by splitting water. Hence, the search for highly efficient catalysts for the HER is a major challenge as efficient hydrogen evolution catalysts are sought to replace catalysts such as platinum. Here we present a low-cost and highly effective electrocatalyst for proper incorporation of the electrocatalyst for hydrogen evolution reaction (HER) with low overpotential, effective charge transfer kinetics, low Tafel slope, and good durability. By using a simple hydrothermal approach to produce Co3(PO4)2.8H2O/CNF, it is possible to attach Co3(PO4)2.8H2O to the surface of carbon nanofibers (CNF), which also exhibit remarkable HER activity at an overpotential of 133 mV obtain the current density of 10 mA/cm2 and 48 mV/decade of Tafel slope. Large electrochemical surface areas and easy charge transfer from Co3(PO4)2.8H2O to the electrode through conductive Co3(PO4)2.8H2O/CNF composites are the reasons for the improved performance of Co3(PO4)2.8H2O/CNF.